87.5k views
3 votes
Answer two questions about Equations A and B:A. 2x-1=5xB. -1=3x1) How can we get Equation B from Equation A?Choose 1 answer:Add/subtract the same quantity to/from both sidesAdd/subtract a quantity to/from only one sideRewrite one side (or both) by combining like termsRewrite one side (or both) using the distributive propertyNEXT QUESTION based on the previous answer, are the equations equivalent? In other words, do they have the same solution?A. Yes B. No

Answer two questions about Equations A and B:A. 2x-1=5xB. -1=3x1) How can we get Equation-example-1
User Tomekwi
by
4.8k points

1 Answer

5 votes

Given data:

The given expression is 2x-1=5x.

The given equation can be written as by subtracting 2x fom both sides.


\begin{gathered} (2x-1)-2x=5x-2x \\ -1=3x \end{gathered}

Thus, equation B can be obtained from A by add/subtract the same quantity to/from both sides, so option (A) is correct.

User Gazala Muhamed
by
4.7k points